Midwifery Care Management for Ms. “K” with Perimenopause at the Community Health Center - Bastian, Nurul Febrianti; Firdayanti,; Saleha, Sitti; Al Kautzar, Anieq Mumthi’ah (Jurnal Midwifery, 2025)
Introduction Perimenopause is a transition period between pre- menopause and post-menopause characterized by natural complaints such as irregular menstruation, hot flushes, and disturbances. Women with irregular menstruation require midwifery care to address the impact of irregular menstrual cycles, such as feelings of anxiety, worry, and varying levels of fear could disturbing activity day living. Therefore, the researcher aims to implement perimenopausal midwifery care management on Mrs “K” at palllangga Health Center, Gowa Regency, following the 7 steps of varney and SOAP. Result of the case study conducted on Mrs. “K” with perimenopause did not encounter any obstacles during giving the treatment on her. Monitoring was conducted six times over a period of approximately body heat during the night, and had difficulty in sleeping. However, after receiving care and understand about perimenopause, she no longer complained and became more accepting of her condition. Conclusion Based on that perimenopausal case study, it is concluded that the 7 steps og varney and SOAP used for the problem- solving process in midwifery care, have successfully provided care, and Mrs. “K” can accept her condition. The role of midwives in this care is essential in providing understanding and information about the preparation and symptoms that will arise during the perimenopausal period.